Abertura econômica e seus efeitos no mercado de trabalho brasileiro na década de 1990 - Hilgemberg, Cleise M. A. Tupich; Guilhoto, Joaquim J. M. (Economia Aplicada, 2004)
This article analyses the effects of the price level stabilization and the economic openness on the Brazilian productive sectors using the yearly input-output tables for the 1990s. Aiming at a better understanding of the changes that had impacted the Brazilian economy, the results were aggregated into seven macro sectors. The study shows that the openness process had an impact on the productive structure with sectors gaining and losing in this process. The agricultural sector went to a process of modernization in which, on one hand it increased its links in the economy, but, on the other hand reduced its capacity of generate employment. The industrial sector became more dependable on imported inputs for its production process, with a reduction in its level of employment. To the service sector was left the task of absorb the workers freed and/or not absorbed by the other sectors.